Histological, Immunohistochemical, and Ultrastructural Characterization of Cartilage in Molly Fish (Poecilia sphenops): Insights into Skeletal Adaptations in Teleosts - Doaa M. Mokhtar; Mohammed A. Abdel-Ghani; Enas A. Abdelhafez; Marco Albano; Khalid M. Alkhodair; Giacomo Zaccone (Fishes)
Cartilage is a crucial component of the vertebrate skeletal system, providing structural integrity, flexibility, and adaptive functions across species. In teleost fish, cartilage exhibits significant morphological and functional diversity, providing specialized biomechanical properties essential for aquatic life. This study presents a detailed histological, immunohistochemical, and ultrastructural investigation of cartilage in molly fish (Poecilia sphenops), identifying five distinct types of cartilage: hyaline-cell, scleral, cell-rich hyaline, elastic cell-rich, and matrix-rich hyaline cartilage. Histological staining techniques revealed notable differences in cellular architecture and composition of the extracellular matrix among the cartilage types. Immunohistochemical analysis demonstrated the expression of S100 protein and acetylcholinesterase (Ach), suggesting their involvement in cartilage regulation and maintenance. Endochondral ossification was observed in the head and gill arches. Electron microscopy provided detailed insights into chondrocyte morphology, interactions between cartilage and the perichondrium, and interactions between telocytes and fibroblasts. The findings enhance our understanding of skeletal adaptations in teleost fish, emphasizing the functional diversity of cartilage in aquatic environments. This study contributes to evolutionary biology and may have implications for regenerative medicine and biomaterials research.